2013
DOI: 10.5114/ceji.2013.34365
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology Th1 and Th2 cytokine profile of CD4 and CD8 positive peripheral blood lymphocytes in nickel contact dermatitis

Abstract: A vast majority of studies investigating cytokine profiles in contact dermatitis (CD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Similar observations on TLR4 and NF-jB involvement were made by Zoroddu et al (2014), Lin et al (2016), Oblak et al (2015) and Peana et al (2017). Almogren et al (2013) observed a predominance of a Th1 phenotype, based on cytokine expression including IL-4 and IL-10, of lymphocytes collected from patients suffering from nickel allergy, in line with commonly accepted mechanisms of contact sensitivity. Also another inflammatory mediator were shown to be induced by nickel: nickel chloride induced the expression of cyclooxygenase-2 (COX-2) mRNA in primary fibroblasts, neutrophils, RAW 264 cells, and THP-1 cells, indicating that nickel ions can induce COX-2 expression in various types of cells (Sato et al, 2016).…”
Section: Immunotoxic Activity Of Nickelsupporting
confidence: 84%
“…Similar observations on TLR4 and NF-jB involvement were made by Zoroddu et al (2014), Lin et al (2016), Oblak et al (2015) and Peana et al (2017). Almogren et al (2013) observed a predominance of a Th1 phenotype, based on cytokine expression including IL-4 and IL-10, of lymphocytes collected from patients suffering from nickel allergy, in line with commonly accepted mechanisms of contact sensitivity. Also another inflammatory mediator were shown to be induced by nickel: nickel chloride induced the expression of cyclooxygenase-2 (COX-2) mRNA in primary fibroblasts, neutrophils, RAW 264 cells, and THP-1 cells, indicating that nickel ions can induce COX-2 expression in various types of cells (Sato et al, 2016).…”
Section: Immunotoxic Activity Of Nickelsupporting
confidence: 84%
“…The patch test reactions were graded from no reaction to +, ++, and +++, depending on the intensity of the reaction in accordance with the recommendations of the International Contact Dermatitis Research Group and the North American Contact Dermatitis Group. 16 Statistical analysis of the data was performed using the Statistical Package for the Social Sciences version 21 (IBM, Armonk, NY, USA). The chi-square test was used to compare gender differences in the parameters.…”
Section: Methodsmentioning
confidence: 99%
“… 13 In India, potassium dichromate and nickel sulfate, in United Arab Emirates, nickel sulfate and fragrance mix, and in Kingdom of Saudi Arabia (KSA), nickel sulfate and p-phenylenediamine have been reported as common skin-sensitizing allergens. 14 - 16 Collectively, these data indicate that nickel sensitization is universally prevalent and is a leading sensitizing allergen. This study aimed to determine common sensitizing agents among patients with ACD attending the allergy clinic at King Khalid University Hospital, Riyadh, KSA.…”
mentioning
confidence: 90%
“…A previous study showed that the Th1 subset of NK T cells has a dominant and critical role in allergy. In addition, the immune response in Ni allergy was skewed towards a Th1 response with a minimal Th2 response [ 32 ]. The Th1 subset of NK T cells may expand locally in response to Ni.…”
Section: The Possible Role Of Nk T Cells In Metal Allergymentioning
confidence: 99%